Current advances in mechanical design and production VII : proceedings of the Seventh Cairo University International MDP Conference ; Cairo-Egypt, February 15-17, 2000 /: proceedings of the Seventh Cairo University International MDP Conference ; Cairo-Egypt, February 15-17, 2000. (2000) - Unknown
No abstract available